Pengenalan Integritas Aplikasi Digital dalam Meningkatkan Kinerja Bisnis sebagai Upaya Mengefektifkan Manajemen - Awaluddin Awaluddin (Jurnal Syntax Admiration, 2024)
This study aims to explore the role of digital application integrity in improving business performance and as an effort to optimize overall management. Through literature reviews and case studies, we identify key factors that affect the integrity of digital applications, such as data security, system reliability, and regulatory compliance. We also evaluate the impact of digital application integrity on operational efficiency, productivity, and customer satisfaction. The results showed that the integrity of digital applications not only prevents security risks and data inaccuracies, but also contributes positively to overall business management. Businesses that focus on maintaining the integrity of their digital applications tend to experience improved performance, efficiency, and competitiveness. Therefore, companies need to prioritize the implementation of policies and practices related to the integrity of digital applications as an integral part of their management strategy.